PROTAC antibiotics: the time is now. (3rd April 2023) - Sarathy, Jickky Palmae; Aldrich, Courtney C.; Go, Mei-Lin; Dick, Thomas
ABSTRACT: Introduction: Novel antibiotics are needed to keep antibiotic resistance at bay and to improve treatment of the many drug-susceptible infections for which current therapies achieve poor cure rates. While revolutionizing human therapeutics, the concept of targeted protein degradation (TPD) by bifunctional proteolysis targeting chimeras (PROTACs) has not yet been applied to the discovery of antibiotics. A major obstacle precluding successful translation of this strategy to antibiotic development is that bacteria lack the E3 ligase-proteasome system exploited by human PROTACs to facilitate target degradation. Areas covered: The authors describe the serendipitous discovery of the first monofunctional target-degrading antibiotic pyrazinamide, supporting TPD as a viable and novel approach in antibiotic discovery. They then discuss the rational design, mechanism, and activity of the first bifunctional antibacterial target degrader BacPROTAC, enabling a generalizable approach to TPD in bacteria. Expert opinion: BacPROTACs demonstrate that linking a target directly to a bacterial protease complex can promote target degradation. BacPROTACs successfully bypass the 'middleman' E3 ligase, providing an entry strategy for the generation of antibacterial PROTACs. We speculate that antibacterial PROTACs will not only expand the target space but may also improve treatment by allowing dosage reduction, stronger bactericidal activity and activity against drug-tolerant 'persisters.'